2013
DOI: 10.2967/jnumed.112.114355
|View full text |Cite
|
Sign up to set email alerts
|

18F-Fluoromisonidazole PET Uptake Is Correlated with Hypoxia-Inducible Factor-1α Expression in Oral Squamous Cell Carcinoma

Abstract: Hypoxia is a common feature of cancer and a prognostic factor for many types of cancer. 18 F-fluoromisonidazole ( 18 F-FMISO) PET can detect tumor hypoxia noninvasively. Hypoxia-inducible factor-1 (HIF-1) is a key player in the transcriptional response to low oxygen tension in many types of cancer. Its activity is mainly dependent on the stability and modification of HIF-1a, which is a composition of HIF-1. However, it is unclear whether 18 F-FMISO PET can identify HIF-1a expression in oral squamous cell carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 32 publications
(74 reference statements)
1
31
1
Order By: Relevance
“…This is not surprising, because Sato et al reported that the FMISO uptake was weakly correlated with the FDG uptake. However, FDG-PET findings do not provide enough information for evaluating reoxygenation in hypoxic tumors, although they can indicate the metabolic activity [6]. Therefore, FDG-PET is not an alternative to FMISO-PET for this purpose.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This is not surprising, because Sato et al reported that the FMISO uptake was weakly correlated with the FDG uptake. However, FDG-PET findings do not provide enough information for evaluating reoxygenation in hypoxic tumors, although they can indicate the metabolic activity [6]. Therefore, FDG-PET is not an alternative to FMISO-PET for this purpose.…”
Section: Discussionmentioning
confidence: 90%
“…F-18 fluoromisonidazole positron emission tomography (FMISO-PET) has been used for noninvasive evaluations of hypoxia, and the FMISO uptake was demonstrated to be correlated with uptake of pimonidazole in animal glioma and with hypoxia-inducible factor-1α (HIF1α) expression in human oral squamous cell carcinoma [5,6]. Several reports have proposed that FMISO uptake is related to patient prognoses [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Bentzen et al [195] , Rasey et al [196] , Bentzen et al [197] , Troost et al [198] Bentzen et al [125] , Gagel et al [126] , Bruehlmeier et al [199] , Lawrentschuk et al [200] , O'Donoghue et al [72] , Piert et al [166] , Sørensen et al [201] , Gagel et al [202] , Carlin et al [203] , Chang et al [204] , Mortensen et al [127] Hatano et al [205] , Huang et al [206] , Huang et al [207] , Oehler et al [208] , Cho et al [209] , Troost et al [210] , Matsumoto et al [136] , Troost et al [198] , Dubois et al [211] Dubois et al [211] , Cherk et al [212] , Riesterer et al [213] , Lehmann et al [214] , Chen et al [215] , Campanile et al [216] , Cheng et al [217] , Sato et al [218] , Norikane et al [219] Cherk et al [212] , Eschmann et al [77] , Gagel et al [82] , Koh et al [87] , Rasey et al [220] , Vera et al…”
Section: F]fmisomentioning
confidence: 99%
“…Koh et al [221] , Liu et al [222] , Yeh et al [223] , Rischin et al [224] , Bentzen et al [125] , Rajendran et al [225] , Gagel et al [126] , Rajendran et al [226] , Hicks et al [227] , Lawrentschuk et al [200] , Loi et al [228] , Thorwarth et al [229] , Rajendran et al [230] , Rischin et al [231] , Thorwarth et al [232] , Zimny et al [124] , Eschmann et al [233] , Gagel et al [202] , Thorwarth et al [234] , Thorwarth et al [235] , Lee et al [236] , Lin et al [237] , Nehmeh et al [238] , Roels et al [239] , Dirix et al [240] , Lee et al [241] , Mortensen et al [127] , Wang et al [56] , Abolmaali et al [242] , Bowen et al [138] , Eary et al [243] , Kikuchi et al [244] , Hugonnet et al [131] , Yamane et al [245] , Mammar et al [246] , Zips et al [247] , Cheng et al [217] , Henriques de Figueiredo et al [248] , Okamoto et al [249] , Sato et al [218] , Segard et al [250] , Tachibana et al [251] , Norikane et al [219] [ Dubois et al …”
Section: F]fmisomentioning
confidence: 99%
“…Tumour hypoxia is known to promote radiotherapy resistance. 75 Fluorine-18 fluoromisonidazole has been widely researched and demonstrated to accumulate in hypoxic cells in head and neck, 76 brain 77 and lung 78 tumours, but its clinical application is limited by a high signal-to-noise ratio. Alternative tracers which act as surrogates for hypoxia include fluorine-18 fluoroazomycin-arabinofuranoside and copper-64 diacetyl-bis(N4-methylthiosemicarbazone).…”
Section: Lung Carcinomamentioning
confidence: 99%